2022
DOI: 10.1177/14759217221103016
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised deep learning method for bridge condition assessment based on intra-and inter-class probabilistic correlations of quasi-static responses

Abstract: Data-driven methods for structural condition assessment have been extensively investigated using deep learning (DL). However, studies on quasi-static response data-based structural health diagnoses are relatively insufficient. The difficulty is that quasi-static response data contain coupled effects of structural parameters and external loads. Considering that the correlation between quasi-static responses subjected to identical external loads is only a function of structural parameters and independent from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Except for the temporal correlation modeling, probability distribution variation informed condition assessment has also been investigated to discover the probabilistic correlation pattern embedded in monitoring data of different structural responses. A DL network comprising two variational autoencoders (VAEs, E 1 - G 1 and E 2 - G 2 ) and two GANs ( G 1 - D 1 and G 2 - D 2 ) was established to model the probabilistic correlations of quasi-static responses of bridges (Xu et al, 2022), as shown in Figure 12. VAEs were designed to model intra-class correlations among either GVDs or CTs, and GANs were designed to model inter-class correlations between GVDs and CTs.…”
Section: Intelligent Structural Health Diagnosismentioning
confidence: 99%
See 4 more Smart Citations
“…Except for the temporal correlation modeling, probability distribution variation informed condition assessment has also been investigated to discover the probabilistic correlation pattern embedded in monitoring data of different structural responses. A DL network comprising two variational autoencoders (VAEs, E 1 - G 1 and E 2 - G 2 ) and two GANs ( G 1 - D 1 and G 2 - D 2 ) was established to model the probabilistic correlations of quasi-static responses of bridges (Xu et al, 2022), as shown in Figure 12. VAEs were designed to model intra-class correlations among either GVDs or CTs, and GANs were designed to model inter-class correlations between GVDs and CTs.…”
Section: Intelligent Structural Health Diagnosismentioning
confidence: 99%
“…Weight sharing (shown as red blocks) was further implemented to ensure that the shared latent space could connect two VAEs. In addition, if the model functions well, PDFs of GVD and CT were supposed to be translated in a cycled manner, which would obey a cycle-consistency constraint (shown as blue arrows).
Figure 12.Schematic of intra-class and inter-class probabilistic correlation modeling between two response groups (Xu et al, 2022).
…”
Section: Intelligent Structural Health Diagnosismentioning
confidence: 99%
See 3 more Smart Citations